The Immediate Effect of Exercising in a Virtual Reality Treadmill (C-Mill) on Skin Temperature of a Man with Lower Limb Amputation - Fábio Marcon Alfieri; Caren da Silva Dias; Daniela Mitiyo Odagiri Utiyama; Denise Vianna Machado Ayres; Linamara Rizzo Battistella (Case Reports in Vascular Medicine)
Background. In amputees, exercising can impact the distribution of body temperature. The aim of this case report is to verify the acute effect of exercising in C-Mill on the temperature distribution in the lower limbs of a man with unilateral transfemoral amputation. Materials and Methods. The thigh and legs of a man with left distal transfemoral amputation were evaluated by thermography (infrared sensor FLIR T650sc) before and after a single 30-minute exercise session performed in a virtual reality treadmill device (C-Mill). Results. The thermographic evaluation showed a difference in temperature between the thighs both before and after the intervention. However, there was a decrease in asymmetry, which went from 4.0°C to 3.1°C in the anterior view and from 5.3°C to 2.9°C in the posterior view, after the intervention. Conclusion. Thermography allowed us to assess the difference in temperature in the lower limbs. Even though the temperature discrepancy has decreased after the single exercise session using the C-Mill, this difference persisted.